Factors influencing the pursuit of personal learning goals in MOOCs. Issue 2 (3rd April 2019) - Henderikx, Maartje; Kreijns, Karel; Castaño Muñoz, Jonatan; Kalz, Marco
ABSTRACT: MOOCs are promising opportunities for lifelong learning, but as promising as these learning opportunities seem, many learners do not succeed in pursuing their personal learning goals. Barriers to learning are the main reason for not finishing the intended (parts of the) MOOCs. This study addressed the question whether the factors age, gender, educational level, and online learning experience affect barriers faced while learning in MOOCs. The results show that it is challenging to combine work and family life with lifelong (online) learning activities, especially for learners in their early adulthood and mid-life. However, more experience with online learning positively affects individuals' ability to cope with these challenges. Also, learners with a lower educational level may experience a lack of knowledge or difficulties with the course content. These findings may serve as input to inform potentially vulnerable learners about these issues and support them in successfully achieving their personal learning goals.